Carbon Nanomaterials: Nitrogen Dopants in Carbon Nanomaterials: Defects or a New Opportunity? (Small Methods 1‐2/2017). Issue 1 (February 2017) - Lee, Won Jun; Lim, Joonwon; Kim, Sang Ouk
Abstract : Heteroatom doping into carbon nanomaterials, including carbon nanotubes, graphene, and graphene nanoribbons is discussed by Sang Ouk Kim and co‐workers in article number 1600014. Nitrogen doping provides new opportunities, including the ability to engineer various physiochemical properties of carbon nanomaterials in a stable manner with different dopant configurations. Pivotal concepts and the next steps in the field are considered.